2010
DOI: 10.1111/j.1464-410x.2009.08760.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient noncompliance before surgery

Abstract: Noncompliance was defined as failure to bring films and/or complete bowel preparation. Patient demographics, socioeconomic and clinical variables were analysed, and reasons for failure to comply with instructions were also recorded. RESULTSTwenty-four of the 101 (24%) patients were not compliant, 13 with films only, seven with bowel preparation only, and four with both sets of instructions. Univariate analysis showed that language and race were factors for noncompliance. Multivariate analysis showed that non-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We found no significant association between preventable cancellations and language or race, which is also in contrast with findings in the adult literature. 9 These differences may be in part because the majority of our patients spoke English, limiting comparisons based on language, and because the sample size was relatively small.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We found no significant association between preventable cancellations and language or race, which is also in contrast with findings in the adult literature. 9 These differences may be in part because the majority of our patients spoke English, limiting comparisons based on language, and because the sample size was relatively small.…”
Section: Resultsmentioning
confidence: 95%
“…This finding is in contrast to the adult literature, where there was a higher risk of noncompliance when patients had a greater distance to travel from home to the hospital. 9 This difference may be due to differences in patient populations or in the complexity of the underlying diagnosis. While patients undergoing circumcision tended to live closer to the hospital than those undergoing other procedures, this difference was not statistically significant, suggesting that distance is an independent risk factor for cancellation.…”
Section: Resultsmentioning
confidence: 99%
“…Ours is not the first study to document these differences, although we are the first to describe them for colectomies. Kaye et al 21 found racial/ethnic minority patients had 17 times the risk of not completing bowel preparation before laparoscopic renal surgery, while studies of colonoscopy preparation found African American patients less likely to perform bowel preparation compared with White patients. 22 , 23 It is critical that future research investigates the cause of this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Reviews into the most effective ways of delivering preoperative information have found the most widely used are pamphlets. 9 An especially worrying finding was that 24% of patients were attending without appropriate escort arrangements in place.…”
Section: Implementation Of Changesmentioning
confidence: 99%
“…It also seemed possible that the period of more than 2 months between patients being given instructions and their actual appointment would affect their compliance. 7 It was therefore decided that two additional reminders of the instructions considered to be most important would be given to patients nearer to their appointment time.…”
Section: Implementation Of Changesmentioning
confidence: 99%